ChemInform Abstract: 2, 6‐Pyridinedicarboxylic Acid as Organocatalyst for the Synthesis of 1, 5‐Benzodiazepines Through One‐Pot Reaction. Issue 46 (24th October 2013) - Lal, Mohan; Basha, R. Sidick; Sarkar, Satavisha; Khan, Abu T.
Abstract Title compounds such as (IV), (VI), and (VIII) are prepared via a three‐component reaction of o‐phenylenediamine (I), aromatic aldehydes and β‐ketoesters.